Venture Capital Financing on MSMEs in PT Sarana Ventura Yogyakarta: A Maslahah Perspective - Rachmat Hidajat (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Purpose: This study aimed to analyze and explain the implementation of venture capital financing at PT. Sarana Ventura on MSMEs in terms of maslahah aspectDesign/Method/Approach: This was descriptive qualitative field research. The subjects were the leaders, the divisions of VCO & investment, legal, and agents of MSMEs at PT. Sarana Ventura in Yogyakarta. The data collection used observation, interview, and documentation techniques. The data analysis consisted of four stages, namely, data collection, data reduction, data display, and conclusion drawing/verification.Findings: The results showed that first, the distribution process of financing conducted by PT. Sarana Ventura is in the form of equity without charging any interest payment but applying the concept of revenue sharing to avoid usury. Second, the distribution process of financing to MSMEs is free from gharar by implementing the principle of the contractual agreement as well as a consensual principle in agreeing. Third, however, the capital distribution to the actors of micro, small and medium enterprises has not yet met the principle of justice because the firm is only willing to provide venture capital to medium scale enterprises which have been running and developing, not for new small scale enterprises (startup).Originality/Values: The main contribution of this study is expected to make venture capital companies more open and competitive in the future in advancing MSMEs.